Reduction in Indium Usage for Silicon Heterojunction Solar Cells in a Short‐Term Industrial Perspective. Issue 8 (16th December 2022) - Jay, Frederic; Gageot, Tristan; Pinoit, Gabriel; Thiriot, Benjamin; Veirman, Jordi; Cabal, Raphael; De Vecchi, Sylvain; Favre, Wilfried; Sciuto, Marcello; Gerardi, Cosimo; Foti, Marina
Abstract : Herein, the interest of a sputtering power reduction during physical vapor deposition (PVD) of the rear side indium‐based transparent conduction oxide (TCO) is investigated to reduce the In consumption in silicon heterojunction (SHJ) solar cells. Halving the supplied power allows for a TCO thickness reduction of 50%. Process fine‐tuning is shown to retain satisfying TCO electrical properties, thus preventing unwanted additional resistance losses despite the drastic reduction in TCO thickness. The produced SHJ solar cells with a 50% reduced TCO thickness show similar performances to those made with the reference process. Using thinner TCO layers at the cell backside is, however, found to come with a bifaciality penalty, which is discussed in detail. Abstract : Herein, the interest of sputtering power reduction during physical vapor deposition of the rear‐side indium‐based transparent conduction oxide (TCO) is investigated to reduce the In consumption in silicon heterojunction solar cells. Halving the supplied power allows for a TCO thickness reduction of 50% and shows similar performances to those made with the reference process.